Collaboration and urban transport: a short review of the special issue - Jesus Gonzalez-Feliu; Cristina Pronello; Josep Maria Salanova Grau; Paulius Skačkauskas (Transport, 2018)
"Collaboration and urban transport: a short review of the special issue" Transport, 33(4), pp. 861-866.